Chevon Milk a project feasibility study - Africa, Gil; Flores, Rommel; Jimenez, Bobbit; Raymundo, Freddie; Umali, Caloy (College of Engineering, 1996)
A feasibility study is the basis for prospective investors in deciding whether or not to pursue investing in a project. As such, a feasibility study must be as accurate and as complete in aiding these investors. In this course, IE 53, we are supposed to fulfill the above mentioned requirements but with an added dimension- the development of an industry that is responsive to the call of nationalism. Necessarily, this industry must be as independent from importations as possible and, conversely, must utilize purely indigenous materials and processes. It is in this light that our group embarked upon the task of ascertaining the feasibility of producing CHEVON PRO, powdered goat's milk.